Cross-age study on secondary school students’ views of stars - Philipp Bitzenbauer; Sarah Navarrete; Fabian Hennig; Malte S. Ubben; Joaquin M. Veith (Physical Review Physics Education Research, 2023)
Research in astronomy education has uncovered that many learners possess limited and fragmented understanding of stars. The corresponding misconceptions manifest in various areas such as star formation, size, the relationship between stars and planets, and their position in space and have been shown to persist across different age groups and educational settings, highlighting the need for further investigation. This paper presents the findings of an empirical study that examines secondary students’ views of stars and their evolution throughout their secondary school education. We designed and evaluated an instrument for assessing students’ views of stars in five domains (stars and the solar system, formation and evolution of stars, general properties and motion of stars, (sub-)stellar objects, as well as color and brightness). The instrument creation process involved several steps, including literature-based item development, an expert survey with faculty members, and a quantitative pilot study with a sample of N=390 secondary school and college students. This process led to a final version of the instrument that exhibits good psychometric properties. We used this new instrument in a cross-age study to investigate the alignment of secondary students’ ideas about stars with scientific views across different stages of secondary education. The sample of this main study comprised a total of N=366 learners, including 148 lower (aged 13–14 years), 151 middle (aged 15–16 years), and 67 upper (aged 17–18 years) secondary school students. Our study findings reveal a progressive development of students’ perspectives on star-related topics throughout their school education: Using analyses of variance and conducting pairwise post hoc comparisons, we observed a statistically significant increase in the proportion of responses aligning with scientific views across all aspects of stars examined in this study, as students progressed from lower secondary to upper secondary levels. We further report on widely held views of stars among our study participants that do not align with the scientific views and discuss the implications of our findings for both educational research and practice.